The electrochemical production of boric acid - (:unkn) unknown (WILEY, 2015)
BACKGROUNDBoric acid (H3BO3) was electrochemically produced from borax pentahydrate (Na2B4O7.5H(2)O) using membrane electrolysis, and a flow diagram of the production process was developed. The effect of different catholyte concentrations (10, 20 and 30% aqueous NaOH) and current densities (1.2, 1.8 and 2.9 kA m(-2)) on current efficiency was studied. The electrical power consumption per ton of boric acid produced was calculated and the qualities of boric acid products were determined. RESULTSThe current efficiency ranged between 94% and 74% depending on operating conditions. Optimum process conditions for electrochemical boric acid production were determined to be 1.8 kA m(-2) current density and 20% aqueous NaOH catholyte concentration. In these conditions, the specific energy consumption for 1 ton of boric acid produced was calculated at 2000 kWh (i.e. specific energy consumption 2000 kWh ton(-1) at 7.5V and 1.8 kA m(-2)). CONCLUSIONSThe production of boric acid by an electrochemical method is more attractive than the current commercial process and other production methods described in the literature. The process is environment friendly since it does not generate solid waste, and oxygen is produced instead of chlorine as in the well-known chlor-alkali process. (c) 2014 Society of Chemical Industry
Keywords: electrochemistry; membrane; production; process development; BORAX